2017
DOI: 10.3892/ol.2017.7211
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of PSAT1 as a potential prognostic factor for predicting clinical outcomes in patients with colorectal carcinoma

Abstract: The aim of the present study was to explore the existence of known or candidate drug-target genes that are upregulated in colorectal cancer (CRC) and may serve as novel prognostic factors or therapeutic targets for this type of malignancy. An in silico analysis was conducted using the Oncomine tool to compare the expression levels of a list of drug-target genes between cancerous and normal tissues in 6 independent CRC cohorts retrieved from the Oncomine database. Phosphoserine aminotransferase 1 (PSAT1) was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…It is reported that PSAT1 expression was remarkably heightened in non-small cell lung cancer (NSCLC) and forecasted poor clinical outcome of NSCLC patients [ 27 ]. Furthermore, PSAT1 is considered as the highest upregulated gene in CRC tumors as well as highly expressed in chemoresistant disease patients [ 28 ]. It has been manifested that GSK3β activity was elevated in cancerous tissues [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that PSAT1 expression was remarkably heightened in non-small cell lung cancer (NSCLC) and forecasted poor clinical outcome of NSCLC patients [ 27 ]. Furthermore, PSAT1 is considered as the highest upregulated gene in CRC tumors as well as highly expressed in chemoresistant disease patients [ 28 ]. It has been manifested that GSK3β activity was elevated in cancerous tissues [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that high PSAT1 expression is implicated in malignant metastasis, chemosensitivity, and poor outcomes. 6,7,17 Inhibiting PSAT1 has been found to enhance the sensitivity of non-small cell lung cancer cells in the absence of glutamine. 18 Dai et al found that silencing PSAT1 reduced angiogenesis and cisplatin resistance via GSK3β/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The latter product is finally converted by phosphoserine phosphatase (PSPH) into serine. Overexpression of PHGDH and PSAT1 due to structural alterations or functional mechanisms was found in many types of cancers [15][16][17][18]. Importantly, some of these tumors are sensitive to targeted SBP inhibition [19,20].…”
Section: Introductionmentioning
confidence: 99%